The use of cardiac rehabilitation services to aid the recovery of patients with bowel cancer: a pilot randomised controlled trial with embedded feasibility study - Gill Hubbard; Julie Munro; Ronan O'Carroll; Nanette Mutrie; Lisa Kidd; Sally Haw; Richard Adams; Angus JM Watson; Stephen J Leslie; Petra Rauchhaus; Anna Campbell; Helen Mason; et al. (National Institute for Health Research, 2016)
Background: Colorectal cancer (CRC) survivors are not meeting the recommended physical activity levels associated with improving their chances of survival and quality of life. Rehabilitation could address this problem. Objectives: The aims of the Cardiac Rehabilitation In Bowel cancer study were to assess whether or not cardiac rehabilitation is a feasible and acceptable model to aid the recovery of people with CRC and to test the feasibility and acceptability of the protocol design. Design: Intervention testing and feasibility work (phase 1) and a pilot randomised controlled trial with embedded qualitative study (phase 2), supplemented with an economic evaluation. Randomisation was to cardiac rehabilitation or usual care. Outcomes were differences in objective measures of physical activity and sedentary behaviour, self-reported measures of quality of life, anxiety, depression and fatigue. Qualitative work involved patients and clinicians from both cancer and cardiac specialties. Setting: Three colorectal cancer wards and three cardiac rehabilitation facilities. Participants: Inclusion criteria were those who were aged > 18 years, had primary CRC and were post surgery. Results: Phase 1 (single site) - of 34 patient admissions, 24 (70%) were eligible and 4 (17%) participated in cardiac rehabilitation. Sixteen clinicians participated in an interview/focus group. Modifications to trial procedures were made for further testing in phase 2. Additionally, 20 clinicians in all three sites were trained in cancer and exercise, rating it as excellent. Phase 2 (three sites) - screening, eligibility, consent and retention rates were 156 (79%), 133 (67%), 41 (31%) and 38 (93%), respectively. Questionnaire completion rates were 40 (97.5%), 31 (75%) and 25 (61%) at baseline, follow-up 1 and follow-up 2, respectively. Forty (69%) accelerometer data sets were analysed; 20 (31%) were removed owing to invalid data. Qualitative study: CRC and cardiac patients and clinicians were interviewed. Key themes were benefits and barriers for people with CRC attending cardiac rehabilitation; generic versus disease-specific rehabilitation; key concerns of the intervention; and barriers to participation (CRC participants only). Economic evaluation: The average out-of-pocket expenses of attending cardiac rehabilitation were £50. The costs of cardiac rehabilitation for people with cancer are highly dependent on whether it involves accommodating additional patients in an already existing service or setting up a completely new service. Limitations and conclusions: The main limitation is that this is a small feasibility and pilot study. The main novel finding is that cardiac rehabilitation for cancer and cardiac patients together is feasible and acceptable, thereby challenging disease-specific rehabilitation models. Future work: This study highlighted important challenges to doing a full-scale trial of cardiac rehabilitation but does not, we believe, provide sufficient evidence to reject the possibility of such a future trial. We recommend that any future trial must specifically address the challenges identified in this study, such as suboptimal consent, completion, missing data and intervention adherence rates and recruitment bias, and that an internal pilot trial be conducted. This should have clear 'stop-proceed' rules that are formally reviewed before proceeding to the full-scale trial. Trial registration: Current Controlled Trials ISRCTN63510637. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 4, No. 24. See the NIHR Journals Library website for further project information.